Compartment-specific importance of glutathione during abiotic and biotic stress - Zechmann, Bernd (Frontiers in Plant Science, 2014)
The tripeptide thiol glutathione (γ-L-glutamyl-L-cysteinyl-glycine) is the most important sulfur containing antioxidant in plants and essential for plant defense against abiotic and biotic stress conditions. It is involved in the detoxification of reactive oxygen species, redox signaling, the modulation of defense gene expression and important for the regulation of enzymatic activities. Even though changes in glutathione contents are well documented in plants and its roles in plant defense are well established, still too little is known about its compartment specific importance during abiotic and biotic stress conditions. Due to technical advances in the visualization of glutathione and the redox state of plants through microscopical methods some progress was made in the last few years in studying the importance of subcellular glutathione contents during stress conditions in plants. This review summarizes the data available on compartment specific importance of glutathione in the protection against abiotic and biotic stress conditions such as high light stress, exposure to cadmium, drought, and pathogen attack (Pseudomonas, Botrytis, Tobacco Mosaic Virus). The data will be discussed in connection with the subcellular accumulation of ROS during these conditions and glutathione synthesis which are both highly compartment specific (e.g. glutathione synthesis takes place in chloroplasts and the cytosol). Thus this review will reveal the compartment specific importance of glutathione during abiotic and biotic stress conditions.